Do psychopathic traits vary with age among women? A cross-sectional investigation - Maurer, J. Michael (The journal of forensic psychiatry & psychology, 2022)
Previous studies with men suggest that certain psychopathic traits vary with age. Specifically, younger men score higher on psychopathic traits measuring impulsive-antisocial behavior, including impulsivity, irresponsibility, and criminal versatility, compared to older men. On the other hand, younger and older men score comparably on psychopathic traits reflecting core personality traits of interpersonal and affective dysfunction, including conning and manipulative behavior and a lack of empathy, guilt, and remorse. However, it is currently not known whether psychopathic traits similarly vary with age among women. This study examined whether psychopathy scores (assessed via the Psychopathy Checklist – Revised [PCL-R]) varied with age among a sample of 501 incarcerated women ranging from 19 to 57 years of age. Consistent with previous studies performed with men, younger women scored higher on psychopathic traits measuring impulsive-antisocial behavior (i.., PCL-R Factor 2, Facet 3, and Facet 4 scores) compared to older women. However, scores on PCL-R Factor 1, Facet 1, and Facet 2, assessing core personality traits, including interpersonal and affective dysfunction, were comparable across women in different age categories. Results obtained in this study suggest the variation of PCL-R Factor 2 traits and the stability of PCL-R Factor 1 traits across the lifespan is invariant across gender.